ANALISIS ANGKUTAN PERSAMPAHAN DI KECAMATAN KUTA - Gabrina T., Silvia; Jaya Wikrama, A.A.; Karnata Mataram, Nyoman; Mahadyatmika W., Arya Ngurah (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 2 Juli 2010)
A study was carried out to analyse the daily solid waste generation in the district of Kuta and to determine the number of trips required transporting the waste to the final disposal site (TPA) in Suwung for the year of 2009, and its estimation until 2015. Data required for the study was collected from on-site surveys and other relevant institutions. The study analysis was based on methods derived from the Indonesian National Standard (SNI) and US Environmental Protection Agency. The study shows that the district of Kuta generated 272.89 m3 solid waste per day in 2009. The solid waste transportation to the final disposal site (TPA) in Suwung is carried out using stationary container system/SCS and hauled container system/HCS. By maximizing the use of the existing solid waste collection trucks owned by DKP Badung Pangkalan Kuta, i.e. the municipal waste management institution for the Kuta District, the transportation to the TPA requires 34 trips/day of SCS, supplemented by 2 and 3 trips/day of HCS for container sites at Jl. Puri Gerenceng, Tuban and Pasar Kuta Unit II respectively. In case no 3R-policy for solid waste management is adopted, the solid waste generation in 2015 is predicted to be 501.89 m3/day. Considering that no more solid waste container location is provided, it would be necessary to increase the number of trips using SCS method to 67 trips/day.
Keywords: solid waste generation, solid waste transportation, stationary container system, hauled container system.